1999
DOI: 10.1093/jn/129.5.928
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Liver γ-Cystathionase Is Required for the Maintenance of Lactation in Rats

Abstract: Liver gamma-cystathionase activity increases in rats during lactation; its inhibition due to propargylglycine is followed by a significant decrease in lactation. This is reversible by N-acetylcysteine administration. To study the role of liver gamma-cystathionase and the intertissue flux of glutathione during lactation, we used lactating and virgin rats fed liquid diets. Virgin rats were divided into two groups as follows: one group was fed daily a diet containing the same amount of protein that was consumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 34 publications
2
39
1
Order By: Relevance
“…Two classes of pyridoxal-5'-phosphate-dependent enzymes, CBS and CSE are responsible for the majority of the endogenous production of H2S in mammalian tissues that use L-cysteine as the main substrate [19,20]. CSE is expressed in a range of mammalian cells and tissues, and it seems to be the main H2S-forming enzyme in the liver, kidney, and cardiovascular system and, CBS is mainly expressed in the liver and central nervous system [8,21]. Florucci et al (2006) have reported expression of CSE mainly in the liver, vascular and nonvascular smooth muscle but, a low level of expression of the CSE transcript, protein, and enzymatic activity is also detectable in the small intestine and stomach of rodents [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two classes of pyridoxal-5'-phosphate-dependent enzymes, CBS and CSE are responsible for the majority of the endogenous production of H2S in mammalian tissues that use L-cysteine as the main substrate [19,20]. CSE is expressed in a range of mammalian cells and tissues, and it seems to be the main H2S-forming enzyme in the liver, kidney, and cardiovascular system and, CBS is mainly expressed in the liver and central nervous system [8,21]. Florucci et al (2006) have reported expression of CSE mainly in the liver, vascular and nonvascular smooth muscle but, a low level of expression of the CSE transcript, protein, and enzymatic activity is also detectable in the small intestine and stomach of rodents [22].…”
Section: Discussionmentioning
confidence: 99%
“…It also uses L-cysteine as an alternative substrate to form H 2 S (4). As a pyridoxal phosphate-dependent enzyme, CSE is expressed in a range of mammalian cells and tissues, and it seems to be the main H 2 S-forming enzyme in the liver, kidney, and cardiovascular system (7,8). Deficiency of H 2 S-producing enzymes results in some disorders such as homocystinuria, which are characterized by mental retardation, skeletal abnormalities, increased urine homocysteine, increased risks of thromboembolism, and early onset of atherosclerosis (9,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Two pyridoxal-5Ј-phosphate-dependent enzymes, cystathionine ␤-synthase (EC 4.2.1.22) and cystathionine ␥-lyase (CSE) 1 (EC 4.4.1.1), are responsible for the endogenous production of H 2 S in mammalian tissues, which use L-cysteine as the main substrate (3)(4)(5). Cystathionine ␤-synthase is a predominant H 2 S-generating enzyme in the brain and nervous system (6), and CSE is mainly expressed in liver, kidney, and vascular smooth muscles (7,8). Cystathionine ␤-synthase and CSE are important for the metabolism of sulfur-containing amino acids (e.g.…”
mentioning
confidence: 99%
“…CBS is a predominant H 2 S-generating enzyme in the brain and nervous tissues (1,12), and CSE is mainly expressed in the liver, kidney, and vascular smooth muscle cells (3,61). Although Hcy has been shown to promote CSE activity at its lower Fig.…”
Section: K Wt 2k Wtmentioning
confidence: 99%